Modeling method and dynamic analysis of turboshaft engine combustor rotor with curvic couplings considering thermal contact resistance under temperature field influence - Yijun Yin; Xing Heng; Haibiao Zhang; Ailun Wang (Results in Engineering)
The dynamic characteristics of the combustor rotor in a turboshaft engine are inevitably affected by temperature. In this combined rotor system, complex curvic couplings interfaces are often involved, leading to discontinuous characteristics in the thermal conduction process. Previous rotor modeling methods do not account for structural discontinuities, particularly the influence of thermal contact resistance at the interface, which poses challenges in accurately constructing the temperature field of rotor model. Aiming at the issues, this paper integrates the finite element method and relies on a curvic couplings geometry model that incorporates rough conical interfaces. Innovatively, it proposes a method for analyzing the thermal contact resistance of the curvic couplings interfaces. Subsequently, a new approach considering the thermal contact resistance of the interface is established for the temperature field of the combined rotor system. And the influence of the temperature field on the natural frequency and rubbing faults of the combined rotor system is studied. Finally experimental verification confirms the rationality and effectiveness of the theoretical method. The results show that with the increase of temperature, the resonance frequency of the combustor rotor system decreases, the amplitude under the rub-impact excitation increases, and the amplitude at the gas turbine disk is the maximum. These methods and conclusions provide a reference for the design research and engineering application of combustor rotor system under temperature field influence.